The Potential of Moringa Oleifera Leaf (Moringa oleifera Lam.) as an Antibacterial: Systematic Literature Review: Moringa Oleifera Leaf - Dwi Nanda, Asri Yuniar (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: The most common type of disease encountered is infectious disease. Antimicrobial substances are known as antibiotics. Misuse of antibiotics can lead to a number of negative outcomes, such as worsening of the drug's side effects, microorganisms becoming resistant to antibiotics, and even death. Methods: Researchers conducted a systematic review that aims to describe the review of the potential of Moringa leaves as antibacterial based on research that has been done. This literature review used six fulltext articles. The literature search technique was carried out on the PubMed and Google Scholar databases. Results: Moringa leaves contain various metabolite compounds such as flavonoids, alkaloids, saponins and tannins which are effective in inhibiting the growth of Gram-positive and Gram-negative bacteria. Moringa leaves can inhibit the growth of S. aureus, E. coli, P. aeruginosa, B. Subtilis, Proteus vulgaris, S. mutans, Streptococcus mutans, Staphylococcus epidedermis, and Salmonella sp. Conclusions: Moringa oleifera Lam. is often referred to as the “miracle tree” because all parts of the plant are beneficial for human health. Moringa leaves have antibacterial potential because they contain metabolite compounds that can inhibit bacterial resistance mechanisms, making them highly effective for treating infections.